PENDEKATAN EKSPERIMENTAL DALAM MERUMUSKAN SINTESIS BARU: INTEGRASI PRINSIP DISTRIBUSI KEKAYAAN ISLAM DAN INOVASI BERORIENTASI MISI BAGI KETAHANAN GLOBAL - Pratama, Dio Septa (Investama : Jurnal Ekonomi dan Bisnis, 2026)
Contemporary global challenges ranging from climate volatility and pandemics to widening social inequality have exposed the limitations of conventional economic paradigms in cultivating systemic resilience. This article argues that effective solutions require a transformative approach that integrates normative ethical frameworks, the dynamic role of the state, and rigorous empirical validation. Against this backdrop, the study introduces and examines an innovative analytical framework that brings together three distinct intellectual traditions: the ethical principles of wealth distribution in Islamic economics as articulated by M. Umer Chapra and M. Nejatullah Siddiqi; the Mission-Oriented Innovation (MOI) theory developed by Mariana Mazzucato to strategically steer innovation towards public purpose; and the experimental, evidence-based approach to policy design advanced by Esther Duflo. Through conceptual analysis and selected illustrative case studies, the article demonstrates how these three paradigms can be coherently integrated into a more comprehensive policy framework. The principles of Islamic economics provide a normative value foundation anchored in justice, equitable distribution, and collective welfare (maslahah) as the ultimate objective (telos). Meanwhile, the MOI framework articulates a strategic role for the state in shaping markets and directing investment in ways that are consistent with these normative goals. The experimental approach serves as a critical instrument for enabling iterative validation and contextual learning, thereby ensuring that the resulting policies are not only effective and efficient but also adaptive to evolving conditions. The findings indicate that the synergy among these three frameworks mitigates the limitations inherent in each approach when applied in isolation, while simultaneously offering a robust foundation for the development of holistic and evidence-based policies. The principal conclusion suggests that the application of an “experimental lens” in support of mission-oriented initiatives grounded in Islamic distributive ethics can significantly enhance both the quality of policy design and the overall impact of interventions aimed at building inclusive and sustainable global resilience. More broadly, this study contributes to the enrichment of interdisciplinary dialogue across the fields of development economics, Islamic economics, and policy innovation.